Unit trust performance: comparison between equity fund and bond fund / Fazana Rusli - Rusli, Fazana (2008)
A unit trust is an investment scheme that pools monies from individuals or institutions who share the same investment and financial objectives. This research attempt study the comparison performance of equity fund and bond fund in Malaysia. The samples are select based on establishment of fund for 5 years (January 2002 until December 2007). The performances of these funds are measured by Descriptive Analysis, Sharp Index, Treynor Index and Jensen's Alpha. Monthly data basis are using in order to collect the data. Sample paired test and independent test are used in order to test the hypothesis. The result shows that, return for both funds is similar. However, in term of risk, the study found equity is more risky compare to bond funds. Bond fund is better than equity fund when the measurement of Treynor and Sharpe Index are using while for Jensen Alpha Index, equity is better than bond fund.